Stellar mergers as the origin of magnetic massive stars - Schneider, Fabian; Röpke, Friedrich (Nature, 2019)
Simulated mergers of two massive stars provide a solution to the long-standing puzzle of the origin of strong magnetic fields in a subset of massive stars.